Recent Progress of Exosome Isolation and Peptide Recognition-Guided Strategies for Exosome Research - Xu, Kun; Jin, Yulong; Li, Yongming; Huang, Yanyan; Zhao, Rui (Frontiers in Chemistry, 2022)
Exosomes are membrane extracellular vesicles secreted by almost all kinds of cells, which are rich in proteins, lipids, and nucleic acids. As a medium of intercellular communication, exosomes play important roles in biological processes and are closely related to the occurrence and development of many diseases. The isolation of exosomes and downstream analyses can provide important information to the accurate diagnosis and treatment of disease. However, exosomes are various in a size range from 30 to 200 nm and exist in complex bio-systems, which provide significant challenges for the isolation and enrichment of exosomes. Different methods have been developed to isolate exosomes, such as the “gold-standard” ultracentrifugation, size-exclusion chromatography, and polymer precipitation. In order to improve the selectivity of isolation, affinity capture strategies based on molecular recognition are becoming attractive. In this review, we introduced the main strategies for exosome isolation and enrichment, and compared their strengths and limitations. Furthermore, combined with the excellent performance of targeted peptides, we summarized the application of peptide recognition in exosome isolation and engineering modification.